Measuring service quality in Indian hospitals: an analysis of SERVQUAL model. (2016) - Kansra, Pooja; Jha, Abhishek Kumar
The quality of service and customer satisfaction are the two most important concepts, which companies need to understand in order to remain competitive in the market. Service quality in healthcare services is important and demands continuous attention by the customers. Keeping this in mind, in the present study an attempt has been made to find out the most important dimensions of quality of service that affects the customer's satisfaction in hospitals. The present study applies the SERVQUAL model given by Parasuraman, for measuring the quality of service in hospitals of Jalandhar region. A structured questionnaire has been formed using the five dimensions (reliability, assurance, tangibles, responsiveness, and empathy) including 25 variables as given by Parasuraman. The data has been collected from the hospitals in Jalandhar region based on random sampling approach; the model has been validated through both confirmatory and exploratory factor analysis approach. The results of the present study did not support the five dimensions of Parasuraman SERVQUAL in India and thus, are reduced to four factors (dimensions) for measuring service quality of hospitals in Jalandhar, India. The policy makers and hospital administrators should focus on these four factors for quality improvement and satisfaction of their customers.